Strategi Bisnis Warung Mama Indah - Pragowo, Hanny Herlambang; Purrohman, Purnama Syae (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research is motivated by consumer needs for Mama Indah's shop in Duren Jaya, East Bekasi, Bekasi City. The problem formulation in this study is how is the marketing strategy of Warung Mama Indah's business?. This type of research is descriptive qualitative research. The subjects in this study were managers, employees, and consumers of Mama Indah's shop. The object of this research is the implementation of the marketing strategy of Mama Indah's warung business. Data collection techniques using observation, interview, and documentation methods. Data analysis techniques using triangulation of sources and techniques. Based on the results of the study, it is stated that the business strategy of Warung Mama Indah is carried out by applying SWOT analysis and the 7P concept, namely: (1) Product, (2) Price, (3) Place, dan (4) Promotion, (5) Phisycal Evedance, (6) People, (7) Process. Keywords: Business Strategy, SWOT Analysis, Marketing Strategy